2020
DOI: 10.3126/jbssr.v5i2.35231
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Investment in Mutual Fund Schemes of Nepal

Abstract: The history of mutual funds in Nepal began with the introduction of “NCM Mutual Fund 2050” in 1993. The Mutual Fund Regulation, 2010 has played an important role in development of Mutual funds as momentous progress can be observed after its implementation. The mutual fund sector has raised Rs. 17.49 billion through public offering and this figure is projected to reach Rs. 19.79 billion by the end of FY 2019/20. Considering the momentous growth in the mutual fund industry this study attempts to analyse the inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…Furthermore, fund manager's qualities were an important factor influencing mutual fund investor's behavior. This study supports the findings of Shrestha and Shrestha (2020), who had found that the level of expertise, credit ratings of fund managers, and their image in the financial market affect mutual fund investment behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, fund manager's qualities were an important factor influencing mutual fund investor's behavior. This study supports the findings of Shrestha and Shrestha (2020), who had found that the level of expertise, credit ratings of fund managers, and their image in the financial market affect mutual fund investment behavior.…”
Section: Discussionsupporting
confidence: 90%
“…The study also partially follows the findings by Shrestha and Shrestha (2020), which showed that ease of investment influences investor's behavior towards mutual funds. However, this study does not completely comply with Nguyen and Nguyen (2019) and Kandel (2020), which state that country governance factors and advertisement's relevance have a significant effect on mutual fund investment behavior.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, the major risk of not being able to attract and satisfy investors for mutual funds still exists, as investors are currently showing an aversion to mutual funds. Fund managers need to tailor mutual fund schemes to specific types of investors to attract investments (Shrestha, 2020).…”
Section: Fund Schemementioning
confidence: 99%
“…The main information source in procurement of the mutual funds are journals and newspapers. The investment schemes being informed by, and in service of, an investor, is a major factor (Shrestha, 2020).…”
Section: Investors' Level Of Knowledgementioning
confidence: 99%
“…In the third rank came the paper "A study of investors' attitude towards mutual fund in Kathmandu city, Nepal" (Bajracharya, 2017) with 13 citations. With eight, six, and five citations, respectively, the articles by Rakhal (2017), Shrestha & Shrestha (2020), and Pant, Ghimire, & Dahal (2022) secured the fourth, fifth, and sixth positions. The remaining articles' citation counts resulted in a lower ranking.…”
Section: Note From Data Basementioning
confidence: 99%